Enhancement of photosynthesis efficiency and yield of strawberry (Fragaria ananassa Duch.) plants via LED systems - Guiamba, Helio Dos Santos Suzana; Zhang, Xiwen; Sierka, Edyta; Lin, Kui; Ali, Muhammad Moaaz; Ali, Waleed M.; Lamlom, Sobhi F.; Kalaji, Hazem M.; Telesiński, Arkadiusz; Yousef, Ahmed Fathy; Xu, Yong (Frontiers in Plant Science, 2022)
Due to advances in the industrial development of light-emitting diodes (LEDs), much research has been conducted in recent years to better understand how plants respond to these light sources. In this study, the effects of different LED -based light regimes on strawberry plant development and performance were investigated. Photosynthetic pigment content, biochemical constituents, and growth characteristics of strawberry plants were studied with a combination of different light intensities (150, 200, and 250 µmol m-2s-1), qualities (red, green, and blue LEDs), and photoperiods (14/10 h, 16/8 h, and 12/12 h light/dark cycles) compared to the same treatment with white fluorescent light. Plant height, root length, fresh and dried shoot weight, chlorophyll a, total chlorophyll/carotenoid content, and most plant yield parameters were highest when illuminated with LM7 [250 µmol m-2 s-1 of a 70% red/30% blue LED light combination and 16/8 h light/dark cycles]. The best results for the effective quantum yield of PSII photochemistry Y(II), photochemical quenching coefficient (qP), and electron transport ratio were obtained with LM8 illumination [250 µmol m-2 s-1 of a 50% red / 20% green / 30% blue LED light combination and 12 h/12 h light/dark cycles] (ETR) obtained. We conclude that strawberry plants require longer and high light intensities with a high red light component for maximum performance and biomass production.